The Effectiveness of the Project Based Learning Model on Web Programming Material in Enhancing Students' Creative Thinking Skills - Muslim, Abdul Aziz; Rasim (Jurnal PPS-TP: Jurnal Pendidikan Analisis, Aplikasi Teori dan Hasil Penelitian, 2024)
This research aims to describe the effectiveness of the Project Based Learning model on Web Programming material in improving students' creative thinking skills. This research is a pre-experiment. The design used in this study is a one-group pretest-posttest group design. The population in this study comprises all X grade students of the TKJ department at SMK 2 Mei Bandarlampung, distributed in one class. The sampling technique used is total sampling. The data collection techniques used are: (1) Test technique, in the form of a written test to measure creative thinking skills; (2) Non-test techniques for collecting student product performance data.The data analysis techniques used are n-gain and parametric statistical tests, namely the dependent sample t-test. The research results show that the n-gain percentage of students in the medium category is 45% and in the high category, namely 35%, the results of the dependent sample t test show a sig. value of 0.001 < 0.05 and the t_(count) value > sig., so there is a significant difference between the pretest score and the posttest score. The conclusion of this study is that the Project Based Learning model is effective in improving the creative thinking skills of X grade TKJ students at SMK 2 Mei Bandarlampung in the even semester of the 2023/2024 academic year